Single-dose modified bloodless del Nido cardioplegia for minimally invasive cardiac surgery - Lee, Heemoon; Kim, Jihoon; Yoo, Jae Suk (Frontiers in Cardiovascular Medicine, 2025)
BackgroundRecent studies demonstrated satisfactory results of del Nido cardioplegia in minimally invasive cardiac surgery (MICS). We aimed to evaluate the efficacy of our modified “bloodless” del Nido cardioplegia in MICS compared to the histidine-tryptophan-ketoglutarate (HTK) solution.MethodsWe retrospectively reviewed 471 patients who underwent minimally invasive cardiac surgery (MICS) in our institution between January 2015 and September 2022. Patients were divided into HTK (n = 96) and bloodless del Nido (n = 375) groups. Using propensity score matching, we matched 72 patients with bloodless del Nido to 72 patients with HTK, based on demographic and operative information.ResultsThere were no significant differences in the baseline characteristics and operative data after matching. The early mortality and morbidities did not differ significantly between the two groups. Freedom from overall mortality did not differ significantly during the follow-up period (97.2% in HTK vs. 98.6 in bloodless del Nido at 2 years, P = 0.56). The two groups had no difference in postoperative lactate levels at 6 and 24 h. Various statistical methods consistently indicated that bloodless del Nido cardioplegia did not increase risks for overall mortality.ConclusionsThe modified bloodless del Nido cardioplegia showed comparable postoperative outcomes in MICS compared with the HTK solution, suggesting its potential as an alternative option for MICS.